Synthesis of pH Responsive Hydrogel Matrices from Guar gum and Poly(acrylamide-co-acrylamidoglycolicacid) for Anti-Cancer Drug Delivery - G. Viswanatha Reddy & , N. Sivagangi Reddy, K. Nagaraja, K.S.V. Krishna Rao (Journal of Applied Pharmaceutical Science, 2018)
Guar gum (GG) is one of the widely available and naturally occurring polymers; it has a wide range of applications in medicine, pharmacy, food, textile and scores of other industrial and commercial sectors due to its rheological adjusting properties. In this paper a pH-responsive GG/poly(acrylamide-co-acrylamidoglycolicacid) (PGAGA) hydrogel matrices were successfully synthesized via simple redox polymerization and N,N-methylene-bis-acrylamide used as cross-linker. 5-fluorouracil (5-FU) is an anticancer drug and it has been loaded into the PGAGA hydrogel matrices via the in-situ method. Pristine as well as 5-FU loaded PGAGA hydrogel matrices have been characterized by Fourier transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC). FTIR and DSC studies have demonstrated that 5-FU is distributed in molecular level throughout the PGAGA hydrogel matrices during in situ loading. Morphology of PGAGA hydrogel matrices was measured by scanning electron microscopic (SEM) analysis. The swelling kinetics of hydrogel matrices were performed in double distilled water and the equilibrium selling is performed at various pH solutions. In vitro release of 5-FU from the PGAGA hydrogel matrices were studied at pH 1.2 and 7.4.
Keywords: Guar gum, Anti-Cancer,5-fluorouracil, Hydrogels,Drug Release.